Comparative experimental analysis of thermodynamic performance of heat pipe and water in glass solar collectors. (July 2020) - Rolon Ortiz, H A; Krenzinger, A; Ferreira, C; Prieb, C
Abstract: Solar energy plays an important role in the alternative energy mix. Solar thermal energy is used in many processes such as domestic water heating, pasteurization, desalination, ambient heating and power generation. There are many devices designed to make use of the radiation coming from the Sun. Evacuated tube solar collectors are one of them. They can be classified according to the employed heat transfer mechanism: direct transfer (water in glass) and indirect transfer (heat pipe). This ongoing work aims to characterize both types of collectors and make an experimental comparative of the thermodynamic performance under the environmental conditions of Porto Alegre, Brazil. An experimental rig was set up with two collectors, one water-in-glass and the other a heat pipe type. Both collectors were connected in series on a tilted plane, together with a global radiation sensor and temperature sensors on interest points namely: inputs and outputs of collectors, air temperature and storage tank. These sensors were connected to a data logger system. Preliminary results show that the heat pipe collector has an average efficiency of 20% superior to the water-in-glass collector.